1999
DOI: 10.1177/026119299902700601
|View full text |Cite
|
Sign up to set email alerts
|

Gastrulating Rat Embryo in a Serum-free Culture Model: Changes of Development Caused by Teratogen 5-Azacytidine

Abstract: Developmental processes in gastrulating rat embryos were investigated by using an original, serum-free, chemically defined model system. 9.5-day-old rat embryos, without extraembryonic membranes, were cultivated at the air–liquid interface in a serum-free medium, with and without a protein supplement, for 2 weeks. A teratogenic, demethylating agent, 5-azacytidine, was added to serum-free and protein-free culture medium and to serum-free medium supplemented with human transferrin. A single dose of 5-azacytidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Obviously, cell cycle dynamics were affected, similarly as in other in vitro studies on rat embryos. 55 Based on the previous research with the metabolically poor protein-free medium and an embryotoxic substance, 26,27,29,32 our results with the 3 most extreme regimes discussed below corroborate the idea that in our model a simple simultaneous assessment of survival and overall growth endpoints can efficiently screen for the most deleterious conditions of the microenvironment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Obviously, cell cycle dynamics were affected, similarly as in other in vitro studies on rat embryos. 55 Based on the previous research with the metabolically poor protein-free medium and an embryotoxic substance, 26,27,29,32 our results with the 3 most extreme regimes discussed below corroborate the idea that in our model a simple simultaneous assessment of survival and overall growth endpoints can efficiently screen for the most deleterious conditions of the microenvironment.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, this in vitro model seems to be as sensitive to this externally applied physical factor as it was to various biologically active substances, among which a DNAdemethylating agent (5-azacytidine) used today in the therapy of myelodysplastic syndrome. 26,27 We may suppose that the similar effects may be obtained at least in the experimental teratoma model in vivo that originates from transplanted embryos to an ectopic environment. 11 In 2011, Yarmolenko et al reviewed CEM43°C and thermal threshold damage data (≥20 -1.5 9 10 4 minutes) mostly in rodent models and found that they are different for various tissues and species.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…When applied in serum-free conditions to the gastrulating rat embryo-proper (consisting of ectoderm, mesoderm, and endoderm), 5azaC impaired survival, growth, and differentiation (11) but in serum-supplemented conditions it promoted differentiation of muscle (12). In a culture of a younger, pre-gastrulating embryo (consisting of epiblast and hypoblast), it promoted differentiation of muscle, cartilage, blood islands, and neural tissue (13).…”
mentioning
confidence: 99%
“…For each investigated group, the orientation/pilot stereological measurement was carried out in order to define the number of fields to be tested (Bulic‐Jakus et al . ). The numerical density of PCNA‐positive cells was determined by the point counting method.…”
Section: Methodsmentioning
confidence: 97%